Laboratory investigation into the use of soundless chemical demolitions agents for the breakage of hard rock - Kelly-Meriam Habib; Isaac Vennes; Hani Mitri (International Journal of Coal Science & Technology, 2022)
Abstract The method of drilling and blasting with explosives is widely used in rock fragmentation applications in the mining industry for mine development and ore production. However, the use of explosives is associated with rigorous safety and environmental constraints as blasting creates toxic fumes, ground vibrations, and dust. This study is focused on the use of Soundless Chemical Demolition Agents (SCDA) as a more environmentally friendly method for rock breakage and a potential replacement of explosives. In this paper, the results of a series of experimental tests are reported to identify the effect of SCDA on hard rock breakage under no load and under uniaxial loading conditions. Stanstead granite prismatic specimens of 152.4 mm (6ʺ) × 152.4–203.2 mm (6–8ʺ) × 406.4 mm (16ʺ) are used to test the influence of borehole size on the time to fracturing with SCDA borehole size of 25.4 mm (1ʺ), 31.75 mm (1.25ʺ) and 38.1 mm (1.5ʺ). It is shown that the fracturing time decreases with increasing borehole size. It is also shown that specimens subjected to uniaxial compression of 5 MPa fracture as early as 7 h after SCDA mixing. A borehole spacing to borehole diameter ratio of 12.8 to 14.6 is suggested for practical applications.